Prospects of Ecotourism Development in Ganderbal District of Jammu and Kashmir - Bhat, Iqbal Ahmad; J, Shyju P (Atna Journal of Tourism Studies, 2014)
Tourism is considered as an important industry in the state of Jammu and Kashmir in general and the Valley of Kashmir in particular. Though the State’s economy is largely depended on agriculture and horticulture, tourism is still considered as the backbone of the economy as it generates large scale employment opportunities. The industry has generated large number of jobs; particularly it has benefitted the younger generation. Boosting the economic activities in the primary, secondary and tertiary sectors in the state, tourism has continued to play a vital role in the economy of the state. The Valley of Kashmir witnesses a huge rush of tourists especially during peak seasons and every corner of Srinagar city is filled with high movement of tourists. The movement of tourists has largely been restricted to Golden Triangle of Kashmir i.e. Srinagar, Phalgam and Gulmarg. The Government has started earmarking other virgin destinations of Kashmir and established authorities for the development of the same, but on the ground level the scene is quite different. It is imperative to assess the carrying capacity of tourist attractions especially new and emerging destinations, in order to minimize the negative impacts of tourism. Keeping in view these considerations, the present work is an attempt to highlight the tourism potential of unexplored areas in Ganderbal District, which have immense potential for ecotourism development.